Retrospective cohort study of the South Tyneside Exercise Referral Scheme 2009–14: predictors of dropout and barriers to adherence. (26th November 2016) - Kelly, Michael C; Rae, Glen C; Walker, Diane; Partington, Sarah; Dodd-Reynolds, Caroline J; Caplan, Nick
Abstract: Background: Exercise Referral Schemes (ERS) are a prevalent method of increasing physical activity levels. However, they suffer from participant dropout and research predicting dropout or barriers to adherence are limited. This study aimed to focus upon the effect of referral characteristics on dropout, dropout predictors and whether self-reported barriers to exercise predict dropout. Methods: ERS data from 2009 to 2014 were retrieved for analysis. Chi-squared and t -tests were used to investigate differences between referral characteristics, and logistic regression used to investigate dropout predictors. Results: Of 6894 participants, 37.8% ( n = 2608) dropped out within 6 weeks and 50.03% ( n = 3449) by the final 12th week. More males adhered ( P < 0.001) with dropouts being significantly younger ( P < 0.001). Dropout predictors were smoking (OR = 1.58, 95% CI: 1.29–1.93) or being a Tier 3 referral (OR = 1.47, 95% CI: 1.25–1.73). Increasing age (OR = 0.98, 95% CI: 0.98–0.99), drinking alcohol (OR = 0.82, 95% CI: 0.71–0.95), secondary care referrals (OR = 0.68, 95% CI: 0.52–0.90), having a lack of motivation (OR = 0.81, 95% CI: 0.69–0.95) or a lack of childcare (OR = 0.69, 95% CI: 0.50–0.95) decreased the likelihood of dropout. Conclusion: ERS dropout continues to be problematic. Smoking and having moderate-high comorbidities predicted dropout. Increasing age and patient-reported barriers of a lack of time or childcare decreased dropout risk. The reasons for dropout require further investigation.